Current and potential soil suitability of barley for crop diversification in IGP region of India: a case study - Ashok Kumar; Vikas Joon; Ritu Nagdev; Jaya N. Surya (Annals of Agricultural Research, 2026)
Soil resources of the study area were evaluated for current and potential soil suitability of barley under existing soil-site regime. Current soil suitability (actual suitability) revealed that 44121.0 ha area evaluated to be highly suitable (S1), whereas remarkable increase (22.9%) in S1 areas has been observed under potential soil suitability regime. Moreover, maximum acreage found to be moderately suitable (S2) for barley production under both current and potential suitability evaluation scenario. Potential soil suitability evaluation recorded significant increase in class S2 area (45.0%) over the existing acreage. The study identified the production constraints and suggested need based intervention including the apt agronomic measures to ensure best utilization of marginally suitable (S3) and presently unfit areas (N1) in due course of time. LMUs based soil management strategies, land evaluation enabled crop planning, and integrated approaches for nutrient and water management, application of soil amendments such as gypsum in salt-affected areas and farm forestry practices need to be included in the research and policy domains to ensure efficient utilization of land resources for sustainable barley production in the study area of IGP region.